2020
DOI: 10.2196/14802
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Intervention Enabled by Mobile Technology on Weight Loss in Patients With Nonalcoholic Fatty Liver Disease: Randomized Controlled Trial

Abstract: Background The prevalence of nonalcoholic fatty liver disease (NAFLD) reaches up to 30% in the Asian adult population, with a higher prevalence in obese patients. Weight reduction is typically recommended for patients at high risk or diagnosed with NAFLD, but is a challenge to achieve. Objective We aimed to evaluate the effect of a lifestyle intervention with a mobile app on weight loss in NAFLD patients. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(99 citation statements)
references
References 47 publications
2
94
0
3
Order By: Relevance
“…Six trials were conducted in middle-income countries, 29,30,31,32,33,34 and the remaining trials were in high-income countries. 27,35,36,37,38,39,40,41,42,43,44,45,46,47,48 The location was unclear for 1 study. 28 Sixteen studies recruited participants with any stage of NAFLD, 27,29,30,31,32,33,34,36,37,39,40,42,43,46,47,48 and 6 recruited only participants with NASH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six trials were conducted in middle-income countries, 29,30,31,32,33,34 and the remaining trials were in high-income countries. 27,35,36,37,38,39,40,41,42,43,44,45,46,47,48 The location was unclear for 1 study. 28 Sixteen studies recruited participants with any stage of NAFLD, 27,29,30,31,32,33,34,36,37,39,40,42,43,46,47,48 and 6 recruited only participants with NASH.…”
Section: Resultsmentioning
confidence: 99%
“…27,35,36,37,38,39,40,41,42,43,44,45,46,47,48 The location was unclear for 1 study. 28 Sixteen studies recruited participants with any stage of NAFLD, 27,29,30,31,32,33,34,36,37,39,40,42,43,46,47,48 and 6 recruited only participants with NASH. 28,35,38,41,44,45 Seven studies recruited participants regardless of BMI, 31,32,33,40,46,47,48 whereas 15 of 22 recruited only people above a minimum BMI (median cutoff, 25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 45 More recently, outcomes from a 6-month RCT using a mobile application to achieve weight loss reported that patients with NAFLD who used the mobile application had a fivefold higher likelihood of achieving ≥5% weight loss compared with the control group. 46 These positive results support a call for large-scale studies of digital health and exercise prescription in patients with risk factors for cardiometabolic disease such as NAFLD.…”
Section: The Future Of Exercise and Pa In Nafldmentioning
confidence: 76%
“…The app also offers support from local dietitians familiar with cultural practices and festivities of local ethnic groups, who are able to consider culturally specific notions of stigma and provide recommendations in line with the cultural norms of users. In a 2020 RCT, 32 the app was found to significantly reduce body weight among patients with nonalcoholic fatty liver disease. In this trial, the Diabetes Lifestyle Intervention using Technology Empowerment (D’LITE) study, we compared the effectiveness of a weight loss lifestyle intervention delivered using the app via in-app coaching by dietitians with usual care, focusing on body weight change and metabolic profiles among Asian patients with type 2 diabetes and overweight or obesity who were not receiving insulin.…”
Section: Introductionmentioning
confidence: 99%